The moderating effect of psychological trust on knowledge spillovers and firms’ open innovation - Huang, Rui; Jin, Jie; Sunguo, Tianxin; Liu, Yongsong (Frontiers in Psychology, 2022)
Based on the characteristics of knowledge attributes, this paper analyzed the data of 180 high-tech firms in China from 2014 to 2020 to deeply explore the effects of explicit knowledge spillover and tacit knowledge spillover on firms' open innovation, and the moderating effect of psychological trust on the relationship between the two. It is found that: first, explicit knowledge spillover and tacit knowledge spillover have an inverted U-shaped relationship with firms' open innovation, i.e., the effect of open innovation increases and then decreases as the degree of knowledge spillover increases; second, psychological trust positively moderates the non-linear relationship between knowledge spillover and firms' open innovation. This paper provides a rational explanation of firms' management behavior from a psychological perspective, and enriches and expands the research related to knowledge spillover, firms' open innovation and psychological trust. It is suggested that firms should pay more attention to inter-organizational trust relationships and pay attention to the psychological growth and development of knowledge employees to improve open innovation in firms.